Predictive Factors of Capsular Contracture in Prepectoral Direct-to-Implant Breast Reconstruction and its Surgical Approach - Kim, Si Youn; Oh, Se Won; Yang, Eun Jung; Song, Seung Yong; Lee, Dong Won (Archives of Plastic Surgery, 2025)
Background Prepectoral direct-to-implant (DTI) is a common implant-based breast reconstruction method used for patients with breast cancer, although patients often present capsular contracture as a common complication. This study aimed to investigate the causes and surgical outcomes of capsular contractures in patients with breast cancer who underwent prepectoral DTI.Methods The medical records of 392 patients (472 breasts) who underwent prepectoral DTI between August 2019 and July 2022 were retrospectively reviewed. Comparative and multivariate analyses were performed to identify risk factors for capsular contracture. The outcomes of patients who underwent surgical procedures were analyzed.Results Of the 472 breasts enrolled in the study, 47 (9.9%) showed capsular contracture. Multivariate analysis revealed that patient age, seroma, rippling, and postmastectomy radiotherapy were independent correlating factors for capsular contracture in prepectoral DTI. Partial capsulectomy was performed on 18 breasts with capsular contracture, which resolved in 88.9% of cases. The mean follow-up period was 14.4 months.Conclusion Age, seroma, rippling, and radiotherapy were independent correlating factors for capsular contracture in prepectoral DTI. Further, partial capsulectomy is recommended as a treatment option to improve results. A better understanding of the causes and surgical outcomes of capsular contracture on prepectoral DTI will help reduce capsular contracture and eventually lead to better outcomes in breast cancer reconstruction.
Keywords: breast reconstruction; implant; capsular contracture